(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Administrative services in Sei Bamban Village are still performed manually, resulting in frequent delays in document verification and archiving and the risk of data loss. The purpose of this research is to use the Unified Approach (UA) approach, which includes the Object-Oriented Analysis (OOA) and Object-Oriented Design (OOD) stages, to design and build a Web-Based Village Administrative Service Information System to address these issues. The developed system’s main features include online letter submission, digital verification by village officials, and a centralized digital archive that stores all service-generated documents electronically. This system accelerates letter verification and streamlines, while document storage becomes more secure and easily accessible. Test results indicate that all system functions function well according to user requirements. This research is expected to support increased efficiency and security of administrative services at the village level through the implementation of integrated information technology.